CAPTURE: A New Predictive Anti-Poaching Tool for Wildlife Protection - Nguyen, Thanh H; Sinha, Arunesh; Gholami, Shahrzad; Plumptre, Andrew; Joppa, Lucas; Tambe, Milind; Driciru, Margaret; Wanyama, Fred; Wanyama, Fred; Rwetsiba, Aggrey; Critchlow, Rob (International Conference on Autonomous Agents & Multiagent Systems (AAMAS'16), 2016)
Wildlife poaching presents a serious extinction threat to many animal species. Agencies (“defenders”) focused on protecting such animals need tools that help analyze, model and predict poacher activities, so they can more effectively combat such poaching; such tools could also assist in planning effective defender patrols, building on the previous security games research. To that end, we have built a new predictive anti-poaching tool, CAPTURE (Comprehensive Anti-Poaching tool with Temporal and observation Uncertainty REasoning). CAPTURE provides four main contributions. First, CAPTURE’s modeling of poachers provides significant advances over previous models from behavioral game theory and conservation biology. This accounts for: (i) the defender’s imperfect detection of poaching signs; (ii) complex temporal dependencies in the poacher’s behaviors; (iii) lack of knowledge of numbers of poachers. Second, we provide two new heuristics: parameter separation and target abstraction to reduce the computational complexity in learning the poacher models. Third, we present a new game-theoretic algorithm for computing the defender’s optimal patrolling given the complex poacher model. Finally, we present detailed models and analysis of realworld poaching data collected over 12 years in Queen Elizabeth National Park in Uganda to evaluate our new model’s prediction accuracy. This paper thus presents the largest dataset of real-world defender-adversary interactions analyzed in the security games literature. CAPTURE will be tested in Uganda in early 2016.